The Dynamics of Housing Demand in the Philippines: Income and Lifecycle Effects - Marife M. Ballesteros (Philippine Institute for Development Studies (PIDS), 2001)
This paper examines the housing consumption pattern of households in the Philippines given their socioeconomic characteristics and the existing conditions in the land and housing market. Two basic issues are examined: one, how is housing adjustment and expenditure associated with income and demographic changes; and two, do housing consumption in the country suggest the presence of significant housing market imperfections or capital market imperfections. The results point to the lack of housing alternatives specifically for the low-income households in the formal housing market. Housing adjustments and the path toward acceptable housing are thus constrained. Estimates of income elasticity show that for most households, an increase in income will not be spent on housing but to meet other basic household needs. This being the case, there has to be a significant increase in income to bring about a significant change in housing conditions. In the long run, economic development may bring about the needed boost in income, however, in the short-run, government has look into alternative forms of low-cost housing. One option is developing the low-cost rental market. Another option is finding innovative financing schemes that would allow low monthly amortization. Lastly, government has to institute ways to effectively reduce the high cost of housing in the country.
Keywords: 330; housing demand; housing consumption pattern; housing elasticity; Wohnungsmarkt; Wohnung; Nachfrage; Einkommenseffekt; Philippinen